Size selectivity and optimal soaking time of hoops and traps targeting the blue swimming crab Callinectes arcuatus in Cuyutlan Lagoon, Mexico (Revista de Biología Marina y Oceanografía, 2021)
The selectivity of two types of commercial fishing gear (crab hoop/traditional gear and rigid rectangular cage traps) targeting blue crabs (Callinectes arcuatus) in Cuyutlan Lagoon, Mexico, was assessed. The effect of soak time on crab catches versus the retention and escape rate of organisms was also evaluated. Results suggested that traps captured larger individuals than hoops. The carapace width of crabs was significantly different between the fishing gears used: 63.9% of crabs caught with hoops were < 95 mm (sizes ranged from 40 to 113 mm) and 40.7% of crabs caught with traps were < 95 mm (range: 49 to 120 mm). Results also showed that catch rates were high during the first two hours and decreased after the third hour. The crabs tended to escape after several hours of soak time. The study found that the traps captured larger crabs than the hoops, suggesting that traps are a suitable fishing gear for catching blue swimming crabs in Cuyutlan Lagoon.